Analysis of the Relationship between Dietary Patterns, Physical Activity and Stress Levels with Blood Glucose Levels in Type 2 Diabetes Mellitus Patients at Sultan Suriansyah Regional Hospital, Banjarmasin - Noviriana, Arika; Firdaus, Syamsul; Muhsinin, Muhsinin (CV. Rayyan Dwi Bharata, 2025)
The increasing number of DM sufferers is caused by hereditary/genetic factors, obesity, lifestyle changes, irregular eating patterns, drugs that affect blood glucose, lack of physical activity, pregnancy, smokers, and stress. Type II DM is a type that is often found in 85-90% of the total DM sufferers found in the elderly group. DM is a world health problem where the incidence, complications and mortality rates are higher in the elderly group than in the younger group. The aim of this study was to analyze the relationship between diet, physical activity and stress levels with blood glucose levels in type 2 diabetes mellitus patients at Sultan Suriansyah Hospital, Banjarmasin. This research design uses a cross sectional method. The statistical tests used are the Spearman rank test and the multiple logistic regression test. The number of samples taken was 92 respondents. The research results showed that there was a relationship between diet, physical activity and stress levels with blood glucose levels in Type 2 Diabetes Mellitus patients (p 0.05) and the factor most related to blood glucose levels was dietary factors with an odds ratio of 9.250. Nurses need to improve health services in providing information that is easily understood by patients and their families directly or using reading media regarding Type 2 Diabetes Mellitus.